Employment Growth and Entrepreneurial Activity in Cities - Zoltán J. Ács; Catherine Armington (Max Planck Institute for Research into Economic Systems, 2004)
Recent theories of economic growth have stressed the role of externalities in generating growth. Using data from the Census Bureau that tracks all employers in the whole U.S. private sector economy, we examine the impact of these externalities, as measured by entrepreneurial activity, on employment growth in Local Market Areas. We find that differences in levels of entrepreneurial activity, diversity among geographically proximate industries, and the extent of human capital are positively associated with variation in growth rates, but the manufacturing sector appears to be an exception.
Keywords: M13; O40; R11; C8; 330; Economic growth; Knowledge spillovers; Entrepreneurship; Industry diversity; Beschäftigung; Städtischer Arbeitsmarkt; Wirtschaftswachstum; Wachstumstheorie; Unternehmer; USA